(untitled) (Revista Electrónica Calidad en la Educación Superior, 2023)
This article presents an analysis of the main functions and characteristics of the academic advisory for self-evaluation and accreditation processes of university programs, carried out by the Center for Academic Evaluation of the University of Costa Rica. It is based on the systematization and critical analysis of the documentary production of the advisory teams from 1999 to 2020. Special focus is given to the evolution of the contributions of academic monitoring to the programs, starting in year 2013. It concludes that the academic monitoring, due to its characteristics, had a direct impact on four aspects, namely: the promotion of academic debate about quality management issues and construction of self-improvement commitments; improvement of the quality management of accredited programs; solution of common needs present in the accredited and reaccredited programs; and generation of accurate information about how the quality systems of the accredited program’s function.